STUDI KOMUNITAS MAKROEPIFIT DI KAMPUS UNIVERSITAS INDONESIA DEPOK, JAWA BARAT - Laela Maulia; Nisyawati Nisyawati (Jurnal Pro-Life, 2017)
A research about macroepifit community was conducted in September 2007 at Universitas Indonesia. The aim of this research is to obtain data of macroepifit’s biodiversity and abundance in northen and southern region of Universitas Indonesia. In addition, the comparison of macroepifit abundance in various tree stage is also obtained. The information that were collected including frequency, density, and macroepifit coverage from each tree in various tree stage.Analysis were done by considering total species, relative frequency, relative density, relative coverage, important value index, Sorensen index, T-test, and correlation between abiotic factor and macroepifit density using Spearman correlation. The result shows that macroepifit in Universitas Indonesia consist of 4 family and 12 species. Drymoglossum piloselloides have the highest abundance in northern region of Universitas Indonesia. D. piloselloides and Pyrrosia lanceolata have the highest abundance in southern region of Universitas Indonesia. The abundance in southern region is higher than northen region because of temperature, humidity, and light intensity in southern region that more suitable for macroepifit growth and development. Keywords :important value index, abundance, community, macroepifit